Government Policy: The Conversion of Protected Forest into Production Forest - Pribadi, Riky; Anwar, Chaidar Awaludin; Ferdiansyah, Ferdy (Unifikasi : Jurnal Ilmu Hukum, 2024)
Land disputes involving protected forests and conservation areas have consistently emerged as issues stemming from land utilisation by local communities. The Ministry of Environment and Forestry plays a fundamental role in addressing these conflicts by altering the status of protected forests into production forests. Accordingly, the study aims to analyse the regulatory framework governing the conversion and to evaluate the effectiveness of the authority, local governments, and the Ministry of Environment and Forestry in facilitating the status change. The research employs a descriptive normative legal approach, drawing on empirical data from surveys, interviews with pertinent parties, and field observations in Majalengka Regency, particularly in Nunuk Village (currently Nunuk Baru Village). The research reveals that regulations and the effectiveness of both local government and ministry policies govern the transformation and use of protected forests into production forests. Government Regulation No. 104 of 2015; the Procedures for Changing Forest Area Designation and Function, is a binding regulation that directly addresses the issues. As a result, the residents of Nunuk Village had no grounds to oppose the change. The effective implementation led to the resolution of the land dispute in Nunuk Baru Village, Maja District, Majalengka Regency, between the local community and Perhutani. The residents' struggle to assert their land rights was ultimately victorious, as the Majalengka local government collaborated with the central government to expedite the resolution of the critical issue. In conclusion, the government must prioritise designating production land that can be effectively and sustainably managed by local communities.